2014
DOI: 10.5539/gjhs.v7n1p16
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge About HIV/AIDS Among High School Students in Erbil City/Iraq

Abstract: Background and Objectives:HIV/AIDS is as a major public health problem which leads to serious challenges to humankind globally. The aim of this study was to assess the knowledge about HIV/AIDS among high school students in Erbil city and to investigate the association between high school students’ socio-demographic characteristics and their level of knowledge about HIV/AIDS.Methods:This descriptive cross-sectional study was carried out in three high schools in Erbil city from February to April 2014. A sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
8
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 6 publications
8
40
8
6
Order By: Relevance
“…Studies found that primary sources of information for students about HIV/AIDS were the print and electronic media [1423, 31], whereas textbooks, and teachers were the next important sources of information [20, 23]. In this current study however, no notable differences were found among students from both the control and intervention areas, in regards to exposure to TV/radio/newspaper.…”
Section: Discussioncontrasting
confidence: 70%
“…Studies found that primary sources of information for students about HIV/AIDS were the print and electronic media [1423, 31], whereas textbooks, and teachers were the next important sources of information [20, 23]. In this current study however, no notable differences were found among students from both the control and intervention areas, in regards to exposure to TV/radio/newspaper.…”
Section: Discussioncontrasting
confidence: 70%
“…12,15 In contrast to the results of current study, lower knowledge levels. [16][17][18] Lower proportion (45%) of the students knew that living with the Hepatitis B or Hepatitis C patient was not a risk factor which was in contrast to result reported by authors. 14 Most of the respondents knew about treatment, post exposure prophylaxis and screening of blood transfusion which was in accordance.…”
Section: Discussioncontrasting
confidence: 73%
“…In a similar study concerning medical students in Iraq in 2013 showed that 71.5% respondents used same needle where 28.5% did not. 19 It is found from this study that our people are more aware about needle sharing than the people of Iraq, so there is no similarity between these two studies regarding needle sharing.…”
Section: Discussionmentioning
confidence: 65%